2009
DOI: 10.1375/ajse.33.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Qualifications and Attitudes Toward Inclusion

Abstract: The inclusion of children with disabilities into the regular education classroom has resulted in many studies on teacher attitudes. Current research has examined teacher beliefs about inclusion, their concerns, and issues pertaining to their ability to cater effectively for children with disabilities in their classrooms. Despite this, there appears to be little research investigating potential associations between teacher attitudes and beliefs toward inclusion, their education levels, and teacher training. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 23 publications
3
26
3
6
Order By: Relevance
“…This result is in line with the previous studies, such as Hastings and Oakford"s (2003), Cornoldi et al, 1998). Hsien, Brown and Bortoli (2009) which revealed teachers with more years of experience had more negative attitudes. In relation to the age levels of teacher analysis of variance showed that there was a statistically significant difference between their age levels that teachers had (F (3,257) = 11.364, P=.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in line with the previous studies, such as Hastings and Oakford"s (2003), Cornoldi et al, 1998). Hsien, Brown and Bortoli (2009) which revealed teachers with more years of experience had more negative attitudes. In relation to the age levels of teacher analysis of variance showed that there was a statistically significant difference between their age levels that teachers had (F (3,257) = 11.364, P=.…”
Section: Discussionsupporting
confidence: 92%
“…With increased numbers of students with a diverse range of disabilities entering mainstream education, the needs of both students and teachers have become an important focus for educational researchers. Literature reviews and research papers over the past five decades have highlighted the progression from negative to positive attitudes of teachers regarding the inclusion of students with disabilities within mainstream education (Avramidis and Norwich, 2002;Bowman, 1986;Hsien, Brown, and Bortoli, 2009;Levins, Bornholt, and Lennon, 2005;Rae, Murray, and McKenzie, 2010;Scruggs and Mastropieri, 1996;Soodak, Podell, and Lehman, 1998;Westwood and Graham, 2003). Over time teachers have voiced their attitudes towards the inclusion of students with disabilities from earlier beliefs supporting the inclusion of students with mild physical disabilities only, to the readiness of educators to accept most students with a wide range of physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…An additional barrier to the successful implementation of inclusion is the lack of teacher education in this area (Forlin & Chambers, 2011). General education teachers have expressed concerns about their ability to implement inclusive practices and Hsien, Brown, and Bortoli (2009) state that teachers have reported low levels of confidence in regard to planning and implementing necessary modifications. Teacher education is believed to play a significant role in preparing teachers to implement inclusive practices (Florian, 2014).…”
Section: Special Education Policy In Practicementioning
confidence: 99%